Effect of elevated temperature on cis-1, 2-dichloroethene dechlorination and microbial community structure in contaminated soils—A biostimulation approach. Issue 2 (April 2020) - Yamazaki, Yuji; Hasegawa, Ai; Tian, Xiaowei; Suzuki, Ichiro; Kobayashi, Takeshi; Shimizu, Takaaki; Inoue, Daisuke; Ike, Michihiko
Highlights: The effects of elevated temperature on cis -1, 2-DCE biostimulation were examined. Elevated temperature enhanced complete dechlorination of cis -1, 2-DCE to ethene. The effect was confirmed in soil and groundwater collected from multiple sites. Growth of multiple Dehalococcoides subgroups was promoted. Thermal effect on microbial communities was smaller than that of nutrient addition. Abstract: Thermally enhanced anaerobic dechlorination has been recently proposed as effective remedial strategy to dechlorinate tetrachloroethene and trichloroethene, as well as their intermediate metabolites, cis -1, 2-dichloroethene and vinyl chloride. To clarify the influence of elevated temperature on cis -1, 2-dichloroethene dechlorination and associated microbial populations under biostimulation condition, repeated cis -1, 2-dichloroethene dechlorination experiments using soil and groundwater samples from three different contaminated sites were performed at 15 and 30 °C. Dechlorination of cis -1, 2-dichloroethene at 30 °C occurred rapidly compared to that at 15 °C, irrespective of the sample source. Elevated temperature contributed to improving the first-order degradation rate constant and shortening the lag time until the initiation of dechlorination. At 30 °C, enhanced growth of different Dehalococcoides different from those observed at 15 °C was found, which may have contributed to faster dechlorination of cis -1, 2-dichloroethene and vinyl chloride. By contrast, microbial community structures in four consortia, which were enriched from two samples under two temperature conditions, reached similar compositions after several subculturings, indicating relatively small influence of elevated temperature on overall microbial communities. The results of this study demonstrate the feasibility of thermally enhancing anaerobic dechlorination under biostimulation to treat various soil and groundwater contaminated with cis -1, 2-dichloroethene.